Mechanical evaluation of matrix type transdermal therapeutic systems containing captopril - (:unkn) unknown (MARMARA UNIV, FAC PHARMACY, 2015)
The objective of this study was to evaluate the mechanical properties of transdermal therapeutic systems (TTS) containing captopril together with synthetic and pH independent polymers, Eudragit RL 100 and RS 100. The formulations were characterized in terms of their adhesiveness and bioadhesiveness by using texture analyser. These optimum formulations were chosen according to the results of our previous study regarding in vitro dissolution and ex vivo diffusion rate studies through excised human skin by using Franz Diffusion Cell. Results indicated that the mechanical properties of the formulations were suitable to be used as a transdermal patch.
Keywords: captopril; transdermal therapeutic system; patch adhesiveness; patch bioadhesiveness; texture analyser; ANGIOTENSIN-CONVERTING-ENZYME; IN-VITRO; EX-VIVO; DELIVERY; DESIGN; INHIBITOR